Effects of the prestress levels on the stiffness of prismatic and star-shaped tensegrity structures. (September 2017) - Cai, Jianguo; Zhou, Yuhang; Feng, Jian; Deng, Xiaowei; Tu, Yongming
On the basis of the introduction of the stiffness matrix of tensegrity structures, the eigenvalue analysis is carried out to study the influence of the prestress level on the stiffness of tensegrity structures. The triangular prismatic tensegrity structure, the star-shaped tensegrity structure and the star-shaped tensegrity structure with a central strut are selected as the numerical examples. The analytical results show that some eigenvalues increase linearly with the prestress level, whereas other eigenvalues firstly increase and then decrease or firstly decrease and then increase with the increase of the prestress level. This is because the stiffness matrix of the tensegrity structures is mainly composed of the material stiffness matrix and geometric stiffness matrix. As the contribution of these two parts of stiffness to eigenvalue models is different, the trends of eigenvalue variations are different with the increase of the prestressed level.